Comparative effects of vortex generators on Ahmed's squareback and minivan car models. (August 2017) - Evrard, Antoine; Cadot, Olivier; Sicot, Christophe; Herbert, Vincent; Ricot, Denis; Vigneron, Rémi
This work aims to evaluate the base suction and drag modifications caused by a boundary layer manipulation due to large scale roughness prior its salient separation. A real car model, a Peugeot 208, and a squareback Ahmed body are both tested and compared in a scale 1 wind tunnel at 120 km/h with road effect and rotating wheels. The roughnesses are vortex generators placed in the boundary layer that develops on the roof of the model. They produce longitudinal vortices in the free shear. Two types of vortex generators are used, wall mounted cylinders for weak disturbances and inclined blades for stronger disturbances. It is found that whatever the vehicle is, the drag is always increased. For the squareback Ahmed body, the base suction is decreased with similar magnitudes for both vortex generators showing a beneficial effect of the vortex generator on the base drag. On the contrary, the base suction is always increased for the real car whatever the vortex generators used. In that case the effects of magnitude depends on the vortex generator types. While the cylinders degrade slightly the base suction with almost no modification in the wake, the blades are able to reduce considerably the bubble length causing a huge increase in drag, lift and base suction.